Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/1943387520952673
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Prognosis of the Teeth in the Mandibular Fracture Line

Abstract: Objective: The aim of this study was to evaluate the prognosis of the teeth in the mandibular fracture line and to analyze the relationship between the degree of displacement of fracture fragments, the relationship of the fracture line to the periodontium, and the relationship between the condition of the teeth at the first postoperative (post-op) year. Methods: A total of 60 teeth from 38 patients (11 female and 27 male) who had erupted teeth in the line of mandibular fracture and were treated with open reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Therefore, type II fractures had a better prognosis for the pulps 5 . A study on the prognosis of teeth in the fracture line showed better pulp outcomes for types II and III involvement 25 . Other studies showed a predominance of type I, followed by type II 11,14 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, type II fractures had a better prognosis for the pulps 5 . A study on the prognosis of teeth in the fracture line showed better pulp outcomes for types II and III involvement 25 . Other studies showed a predominance of type I, followed by type II 11,14 .…”
Section: Discussionmentioning
confidence: 96%
“…Other studies showed a predominance of type I, followed by type II 11,14 . However, it has been described that the type of fracture according to the relationship between the fracture line and the periodontium did not influence the occurrence of complications, with greater importance of the location of the fracture 11,25 …”
Section: Discussionmentioning
confidence: 97%
“…[59][60][61] A systematic review by Fernandes et al similarly failed to show any statistically significant difference in complication rates. 62 When teeth in the line of the fracture impair adequate reduction of the bony segments, are involved in an infected fracture, are mobile due to fracture or periodontal disease, have associated drainage, periapical radiolucency, or are themselves fractured, they should be removed. [61][62][63][64] For teeth otherwise involved in the lines of fractures, recent recommendations advise clinical and radiographic monitoring for at least 1 year and avoid unnecessary, costly endodontic procedures.…”
Section: Special Considerationsmentioning
confidence: 99%
“…62 When teeth in the line of the fracture impair adequate reduction of the bony segments, are involved in an infected fracture, are mobile due to fracture or periodontal disease, have associated drainage, periapical radiolucency, or are themselves fractured, they should be removed. [61][62][63][64] For teeth otherwise involved in the lines of fractures, recent recommendations advise clinical and radiographic monitoring for at least 1 year and avoid unnecessary, costly endodontic procedures. 63 When a symptomatic tooth needs to be removed, it should ideally be removed once an adequate healing period has occurred, typically at a minimum of 3 months following reduction.…”
Section: Special Considerationsmentioning
confidence: 99%
See 1 more Smart Citation